Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1038/sj.ijo.0803360
|View full text |Cite
|
Sign up to set email alerts
|

Reducing weight increases postural stability in obese and morbid obese men

Abstract: Objective: To investigate the effect of weight loss on balance control in obese and morbid obese men. Methods: In a longitudinal and clinical intervention study, postural stability was measured with a force platform before and after weight loss in men. Weight loss was obtained in obese men (mean body mass index (BMI) ¼ 33.0 kg/m 2 ) by hypocaloric diet until resistance and in morbid obese men (mean BMI ¼ 50.5 kg/m 2 ) by bariatric surgery. Morbid obese men were tested before surgery, and 3 and 12 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
148
3
25

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(199 citation statements)
references
References 41 publications
18
148
3
25
Order By: Relevance
“…In addition, it should be noted that the overweight group swayed more than the normal weight group; however, this difference was not significant (i.e., Table 2). However, we have previously demonstrated that postural stability is strongly related to the amount of body weight Teasdale et al 2007). Therefore, in this study, even if our overweight group is not significantly different from the other groups, as can be clearly seen in Fig.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In addition, it should be noted that the overweight group swayed more than the normal weight group; however, this difference was not significant (i.e., Table 2). However, we have previously demonstrated that postural stability is strongly related to the amount of body weight Teasdale et al 2007). Therefore, in this study, even if our overweight group is not significantly different from the other groups, as can be clearly seen in Fig.…”
Section: Discussionmentioning
confidence: 59%
“…There are other factors that might also increase a risk of falling, for example, sarcopenia (muscle wasting) and dynapenia (muscular strength loss), have been observed in these populations, and this contributes to the deterioration in physical capacity (Baumgartner et al 1998;Cruz-Jentof et al 2010;Clark and Manini 2010;Visser 2011). The effect of obesity on balance control has been previously observed and described elsewhere (McGraw et al 2000;Maffiuletti et al 2005;Greve et al 2007;Teasdale et al 2007;Menegoni et al 2009;Handrigan et al 2010), and the original contribution of this study is the demonstration of the added effect of obesity on balance control in older women aged 65-80 years old. Furthermore, despite the observed differences in balance control, it is important to note that these individuals were living independently.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings indicate that a high BMI is associated with reduced postural control and balance after a TKR. Because being overweight or obese is a risk factor for poor postural stability (56)(57)(58), and because changes in body weight influence balance control (59,60), it is reasonable to expect that overweight and obese patients perform more poorly in the FRT and SLS test compared with patients with a normal BMI, because such tasks are highly dependent on postural stability and balance control. Previous studies have shown that the performance of postural stabilitydependent mobility tasks improves after balance-based post-TKR rehabilitation (24,38), which is consistent with the significant improvements in the FRT and SLS test results for all of the BMI groups at the 2-month and 6-month post-TKR followup assessments in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In post-menopausal women, Hita-Contreras et al [5] found that a body mass index higher than 25 kg m -2 can be already considered as a risk factor for falls. Tesdale et al [6], in obese people observed a strong linear relationship between the magnitude of the weight loss and the improvement in balance control, or a con irmation that body mass is a strong conditioning factor of the static and dynamic posture.…”
Section: Introductionmentioning
confidence: 99%